Analisis Pengaruh Koneksi Militer terhadap Tingkat Suku Bunga di Perusahaan-Perusahaan Indonesia - Budi Harsono; Christina Kwok (Global Financial Accounting Journal, 2019)
The purpose of this study is to provides direct empirical evidence on the effect of military connections on interest rate for listed firms in Indonesia. Purposive sampling was implemented in this study. This study used 2.107 data companies listed on IDX in the period 2013-2017. The results show that firm size and growth have the significant impact on interest rate in both positive and negative ways. While military connections, return on assets, leverage, and market to book value were not able to affect interest rate activity significantly